CETP and SGLT2 inhibitor combination therapy increases glycemic control: a 2x2 factorial Mendelian randomization analysis - Khomtchouk, Bohdan B.; Sun, Patrick; Maggio, Zane A.; Ditmarsch, Marc; Kastelein, John J. P.; Davidson, Michael H. (Frontiers in Endocrinology, 2024)
Cholesteryl ester transfer protein (CETP) inhibitors have been investigated in clinical trials to treat hyperlipidemia and have been associated with decreased risk of new-onset diabetes. This makes them a prospective cardiovascular drug candidate that can potentially be repurposed to treat metabolic disease. Notably, as an oral drug it may be viable to supplement existing oral drugs such as sodiumglucose cotransporter 2 (SGLT2) inhibitors before patients must take injectable drugs such as insulin. In this study, we perform a 2x2 factorial Mendelian Randomization analysis of 233,765 participants in the UK Biobank to investigate whether joint genetic CETP and SGLT2 inhibition increases glycemic control over inhibition of just one. We find that genetic inhibition of both CETP and SGLT2 leads to significantly lower glycated hemoglobin levels than control, SGLT2 inhibition alone, and CETP inhibition. Furthermore, joint CETP and SGLT2 inhibition is associated with decreased incidence of diabetes compared to control and SGLT2 inhibition alone. Our results suggest that CETP and SGLT2 inhibitor therapy may improve glycemic control over SGLT2 inhibitors alone. Future clinical trials can explore whether CETP inhibitors can be repurposed to treat metabolic disease and provide an oral therapeutic option to benefit high-risk patients before escalation to injectable drugs such as insulin or glucagon-like peptide 1 (GLP1) receptor agonists.